Risk stratification of elderly patients with acute pulmonary embolism. (16th July 2019) - Klingenberg, Roland; Schlager, Oliver; Limacher, Andreas; Méan, Marie; Vuilleumier, Nicolas; Beer, Juerg H.; Staub, Daniel; Frauchiger, Beat; Aschwanden, Markus; Lämmle, Bernhard; Righini, Marc; Egloff, Michael; et al.
Abstract: Background: Combining high‐sensitivity cardiac Troponin T (hs‐cTnT), NT‐pro‐B‐type natriuretic peptide (NT‐proBNP) and high‐sensitivity C‐reactive protein (hs‐CRP) may improve risk stratification of patients with pulmonary embolism (PE) beyond the PESI risk score. Methods: In the prospective multicentre SWITCO65+ study, we analysed 214 patients ≥ 65 years with a new submassive PE. Biomarkers and clinical information for the PESI risk score were ascertained within 1 day after diagnosis. Associations of hs‐TnT, NT‐proBNP, hs‐CRP and the PESI risk score with the primary endpoint defined as 6‐month mortality were assessed. The discriminative power of the PESI risk score and its combination with hs‐cTnT, NT‐proBNP and hs‐CRP for 6‐month mortality was compared using integrated discrimination improvement (IDI) index and net reclassification improvement (NRI). Results: Compared with the lowest quartile, patients in the highest quartile had a higher risk of death during the first 6 months for hs‐cTnT (adjusted HR 10.22; 95% CI 1.79‐58.34; P = 0.009) and a trend for NT‐proBNP (adjusted HR 4.3; 95% CI 0.9‐20.41; P = 0.067) unlike hs‐CRP (adjusted HR 1.97; 95% CI 0.48‐8.05; P = 0.344). The PESI risk score (c‐statistic 0.77 (95% CI 0.69‐0.84) had the highest prognostic accuracy for 6‐month mortality, outperforming hs‐cTnT, NT‐proBNP and hs‐CRP (c‐statistics of 0.72, 0.72, and 0.54), respectively. Combining all three biomarkers had no clinically relevant impact on risk stratification when added to the PESI risk score (IDI = 0.067; 95% CI 0.012‐0.123; P = 0.018; NRI = 0.101 95% CI −0.099‐0.302; P = 0.321). Conclusions: In elderly patients with PE, 6‐month mortality can adequately be predicted by the PESI risk score alone.